FREQUENCY OF HEART RHYTHM DISORDERS IN CHILDREN WITH RARE FORMS OF CARDIOMYOPATHIES (International journal of artificial intelligence, 2024)
Rare forms of CMP in children include non-compact left ventricular cardiomyopathy and restrictive cardiomyopathy. The difficulties in diagnosing non-compact and restrictive cardiomyopathy are due to the paucity of sound symptoms, the variability of clinical manifestations and the possibility of an asymptomatic course for a long time.